2016
DOI: 10.17795/ccn-5098
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of an Empowerment Program on the Stress Among Mothers of Neonates Undergoing Colostomy

Abstract: Background: It is difficult and stressful for mothers to care for neonates undergoing colostomy. The mothers of neonates undergoing colostomy usually lack knowledge and skills of home caring procedures; hence, they may experience great stress. Objectives: The current study aimed to evaluate the effects of an empowerment program on the stress level of the mothers of neonates undergoing colostomy. Patients and Methods:This clinical trial was conducted in the neonatal intensive care units of the Bahrami, Mofid, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 6 publications
0
7
0
3
Order By: Relevance
“…Dabas et al (2016) determined that educating parents with pediatric colostomy video teaching program and Dhanalakshmi (2016) instructional package are effective in colostomy management [25,26]. Goudarzi et al (2016) found that the empowerment program signi cantly reduced the stress levels of parents [21]. David et al (2020) determined that colostomy patients and their families need training to reduce their psychosocial concerns (eg, coping with an ostomy) as well as learn colostomy care [27].…”
Section: Emotional Distressmentioning
confidence: 99%
See 1 more Smart Citation
“…Dabas et al (2016) determined that educating parents with pediatric colostomy video teaching program and Dhanalakshmi (2016) instructional package are effective in colostomy management [25,26]. Goudarzi et al (2016) found that the empowerment program signi cantly reduced the stress levels of parents [21]. David et al (2020) determined that colostomy patients and their families need training to reduce their psychosocial concerns (eg, coping with an ostomy) as well as learn colostomy care [27].…”
Section: Emotional Distressmentioning
confidence: 99%
“…They were mainly ashamed of odor while taking care of their children. Reports in the literature have determined that as a result of having pediatric colostomy, parents are embarrassed and experience a diminished quality of life; in most cases, the mother is more affected than father [8, 14,21]. The literature reports that when parents of children with a colostomy rst encounter the colostomy bag, they feel afraid, helpless, uncertain and anxious.…”
Section: First Meetingmentioning
confidence: 99%
“…Todo esse cuidado deve ser repassado individualmente em forma de conversa (dialógo) e reforçado com uso de materiais educativos impressos, videos, brinquedo terapêntico (CHU;DUONG, 2015;DABAS et al, 2016;GOUDARZI et al, 2016).…”
Section: Plano De Cuidadosunclassified
“…Em três estudos da amostra, os autores utilizaram como estratégias de educação em saúde: um programa de educação estruturado, um programa educacional utilizando vídeo com informações inerentes a estomização, e um programa de capacitação educacional para pais, utilizando grupo de intervenção e o grupo controle (CHU;DUONG, 2015;DABAS et al, 2016;GOUDARZI et al, 2016).…”
Section: Inserção Socialunclassified
See 1 more Smart Citation